European multicentre study to define disease activity criteria for systemic sclerosis. II. Identification of disease activity variables and development of preliminary activity indexes. Issue 6 (1st June 2001) - Valentini, G; Della Rossa, A; Bombardieri, S; Bencivelli, W; Silman, A J; D'Angelo, S; Cerinic, M Matucci; Belch, J F; Black, C M; Bruhlmann, P; Czirják, L; De Luca, A; et al.
Abstract : OBJECTIVE: To develop criteria for disease activity in systemic sclerosis (SSc) that are valid, reliable, and easy to use. METHODS: Investigators from 19 European centres completed a standardised clinical chart for a consecutive number of patients with SSc. Three protocol management members blindly evaluated each chart and assigned a disease activity score on a semiquantitative scale of 0–10. Two of them, in addition, gave a blinded, qualitative evaluation of disease activity ("inactive to moderately active" or "active to very active" disease). Both these evaluations were found to be reliable. A final disease activity score and qualitative evaluation of disease activity were arrived at by consensus for each patient; the former represented the gold standard for subsequent analyses. The correlations between individual items in the chart and this gold standard were then analysed. RESULTS: A total of 290 patients with SSc (117 with diffuse SSc (dSSc) and 173 with limited SSc (lSSc)) were enrolled in the study. The items (including Δ-factors—that is, worsening according to the patient report) that were found to correlate with the gold standard on multiple regression were used to construct three separate 10-point indices of disease activity: ( a ) Δ-cardiopulmonary (4.0), Δ-skin (3.0), Δ-vascular (2.0), and Δ-articular/muscular (1.0) for patients with dSSc; ( b ) Δ-skin (2.5), erythrocyte sedimentation rate (ESR) >30 mm/1st h (2.5), Δ-cardiopulmonary (1.5), Δ-vascular (1.0), arthritis (1.0), hypocomplementaemia (1.0), and scleredema (0.5) for lSSc; ( c ) Δ-cardiopulmonary (2.0), Δ-skin (2.0), ESR >30 mm/1st h (1.5), total skin score >20 (1.0), hypocomplementaemia (1.0), scleredema (0.5), digital necrosis (0.5), Δ-vascular (0.5), arthritis (0.5), Tlco <80% (0.5) for all patients with SSc. The three indexes were validated by the jackknife technique. Finally, receiver operating characteristic curves were constructed in order to define the value of the index with the best discriminant capacity for "active to very active" patients. CONCLUSIONS: Three feasible, reliable, and valid preliminary indices to define disease activity in SSc were constructed.